IMPROVING THE KYC ONBOARDING PROCESS USING BUSINESS PROCESS RE-ENGINEERING: A CASE STUDY AT BANK ANGGREK - Fadhila, Aisha
The Know-Your-Customer (KYC) onboarding in the customer acquisition process became an issue in an Indonesian branch of a prominent global bank. In 2023, Bank Anggrek received a significant complaint from one of its major clients expressing discontent with the inefficiency of the bank’s KYC onboarding process. This complaint brought the KYC onboarding process under scrutiny from senior management. From 2019 to 2023, the number of clients expressing dissatisfaction with the bank’s KYC onboarding process steadily increases. At the same time period, the bank also experienced a rise in the number of potential new clients dropping their requests during the KYC onboarding process.